The Dynamic Role of NK Cells in Liver Cancers: Role in HCC and HBV Associated HCC and Its Therapeutic Implications - Sajid, Muhammad; Liu, Lianxin; Sun, Cheng (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) remains an important complication of chronic liver disease, especially when cirrhosis occurs. Existing treatment strategies include surgery, loco-regional techniques, and chemotherapy. Natural killer cells are distinctive cytotoxic lymphocytes that play a vital role in fighting tumors and infections. As an important constituent of innate immune system against cancer, and phenotypic and functional deviations of NK cell have been demonstrated in HCC patients who also exhibit perturbation of the NK-activating receptor/ligand axis. The rate of recurrence of tumor-infiltrating and circulating NK cells are positively associated with survival benefit in HCC and have prognostic significance, suggesting that NK cell dysfunction is closely related to HCC progression. NK cells are the first-line effector cells of viral hepatitis and play a significant role through directly clearing virus-infected cells or through activating antigen-specific T cells by producing IFN-γ. In addition, chimeric antigen receptor (CAR) engineered NK cells suggest an exclusive opportunity to produce CAR-NKs with several specificities with fewer side effects. In present review, we comprehensively discuss about the innate immune landscape of liver, particularly NK cells and the impact of tumor immune microenvironment (TIME) on function of NK cells and biological function of HCC. Furthermore role of NK cells in HCC and HBV induced HCC have also been comprehensively elaborated. We also elaborate available NK cell-based immunotherapeutic approaches in HCC treatment and summarize current advancement for treatment of HCC. This review will facilitate researchers to understand the importance of innate immune landscape of NK cells and lead to devise innovative immunotherapeutic strategies for the systematic treatment of HCC.